Differential gene expression elicited by children in response to the 2015–16 live attenuated versus inactivated influenza vaccine. Issue 49 (14th December 2017) - Cole, Kelly Stefano; Martin, Judith M.; Horne, William T.; Lin, Chyongchiou J.; Nowalk, Mary Patricia; Alcorn, John F.; Zimmerman, Richard K.
Highlights: Selected RNA sequencing was studied before and after LAIV and IIV administration in children. At Day 7 after IIV vaccination, 7 genes were significantly down-regulated. At Day 7 after LAIV vaccination, 5 genes were significantly up-regulated and 3 were down-regulated. Only two genes demonstrated similar patterns of regulation in both groups (down-regulated). Abstract: Background: In recent influenza seasons, the live attenuated influenza vaccine (LAIV) has not demonstrated the same level of vaccine effectiveness as that observed among children who received the inactivated influenza vaccine (IIV). To better understand this difference, this study compared the mRNA sequencing transcription profile (RNA seq) in children who received either IIV or LAIV. Methods: Children 3–17 years of age receiving quadrivalent influenza vaccine were enrolled. Blood samples were collected on Day 0 prior to vaccination and again on Day 7 (range 6–10 days) following vaccination. Total RNA was isolated from PAXgene tubes and sequenced for a custom panel of 89 transcripts using the TruSeq Targeted RNA Expression method. Fold differences in normalized RNA seq counts from Day 0 to Day 7 were calculated, log2 transformed and compared between the two vaccine groups. Results: Of 72 children, 46 received IIV and 26 received LAIV. Following IIV vaccination, 7 genes demonstrated significant differential expression at Day 7 (down-regulated). In contrast, following LAIV vaccination, 8 genes demonstrated significant differential expression at Day 7 (5 up-regulated and 3 down-regulated). Only two genes demonstrated similar patterns of regulation in both groups. Conclusions: Differential regulation of genes was observed between 2015–16 LAIV and IIV recipients. These results help to elucidate the immune response to influenza vaccines and may be related to the difference in vaccine effectiveness observed in recent years between LAIV and IIV.